2017
DOI: 10.2147/copd.s137806
|View full text |Cite
|
Sign up to set email alerts
|

Identification of thyroxine-binding globulin as a candidate plasma marker of chronic obstructive pulmonary disease

Abstract: Biomarkers for the management of chronic obstructive pulmonary disease (COPD) are limited. The aim of this study was to explore new plasma biomarkers in patients with COPD. Thyroxine-binding globulin (THBG) was initially identified by proteomics in a discovery panel and subsequently verified by enzyme-linked immunosorbent assay in another verification panel with a 1-year follow-up. THBG levels were elevated in patients with COPD (9.2±2.3 μg/mL) compared to those of the controls (6.6±2.0 μg/mL). Receiver operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Outpatients with COPD (n=40) were enrolled in the clinic of Peking University Third Hospital. The inclusion criteria have been previously depicted, 23 , 24 and the brief description was shown as follows: 1) males 40–80 years of age; 2) a smoking history of >10 pack-years; 3) diagnosis of COPD according to the Global Initiative for Obstructive Lung Disease (GOLD); 1 , 25 4) lack of exacerbation events or use of systemic antibiotics within the past 3 months; and 5) lack of severe organ dysfunction or active disease. The control group (n=19) consisted of male smokers without COPD.…”
Section: Methodsmentioning
confidence: 99%
“…Outpatients with COPD (n=40) were enrolled in the clinic of Peking University Third Hospital. The inclusion criteria have been previously depicted, 23 , 24 and the brief description was shown as follows: 1) males 40–80 years of age; 2) a smoking history of >10 pack-years; 3) diagnosis of COPD according to the Global Initiative for Obstructive Lung Disease (GOLD); 1 , 25 4) lack of exacerbation events or use of systemic antibiotics within the past 3 months; and 5) lack of severe organ dysfunction or active disease. The control group (n=19) consisted of male smokers without COPD.…”
Section: Methodsmentioning
confidence: 99%
“…To date, limited work has been carried out on the role of TBG in the lung environment; increased TBG levels have been associated with the severity of computed tomographyassessed emphysema [97]. Furthermore, TBG was identified as a novel plasma marker of COPD using isobaric tag for relative and absolute quantification (iTRAQ) proteomics [98]. Elevated plasma TBG levels were detected in patients with COPD compared to control subjects and correlated with reduced lung function and acute exacerbations [98].…”
Section: Serpina7mentioning
confidence: 99%
“…Furthermore, TBG was identified as a novel plasma marker of COPD using isobaric tag for relative and absolute quantification (iTRAQ) proteomics [98]. Elevated plasma TBG levels were detected in patients with COPD compared to control subjects and correlated with reduced lung function and acute exacerbations [98]. 4.1.5.…”
Section: Serpina7mentioning
confidence: 99%
“…Diao et al found that COPD patients with higher baseline THBG levels had a greater risk of acute exacerbations (AEs) than those with lower THBG levels. These results indicated that THBG could assist in the management of stable stages and AEs in COPD patients [32]. And fetuin-B could identify more severe grades of lung function in COPD patients and predict the occurrence of AEs or frequent AEs, which could be a complement to other markers for the diagnosis of COPD [33].…”
Section: Plasma and Serummentioning
confidence: 89%